The Effect of Soybean Extract Substitution on Physical and Sensory Quality Pukis Cake - Dinda Lestari; Nur Riska; Alsuhendra Alsuhendra (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to analyze the effect of substituting instant coconut milk with soy milk on the physical quality and sensory quality of pukis cakes in order to determine the optimum formula for producing a product with good quality. The research method used was an experiment with three levels of soy milk substitution, namely 80%, 90%, and 100%. Physical tests were conducted by measuring height for expansion power and measuring hardness levels with a texture profile analyzer. Meanwhile, sensory quality was tested through organoleptic tests by 45 semi-trained panelists from Culinary Education students. Physical quality data were analyzed using the One Way ANOVA test and followed by Duncan's Multiple Range Test (DMRT), while sensory quality data were analyzed using the Kruskal-Wallis test and followed by Tukey's test. The results of statistical analysis showed that soybean milk substitution had a significant effect on the expansion, hardness level, and sensory characteristics of soybean flavor in pukis cakes. An increase in the percentage of soybean milk and a decrease in the use of coconut milk tended to produce pukis cakes with higher expansion, lower hardness values, and stronger soybean flavor. The formula with 80% soybean milk substitution is recommended as the optimal formulation because it produces the best balance between the physical quality and sensory quality of pukis cakes.